2012
DOI: 10.1038/mtna.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

Systemic RNAi-mediated Gene Silencing in Nonhuman Primate and Rodent Myeloid Cells

Abstract: Leukocytes are central regulators of inflammation and the target cells of therapies for key diseases, including autoimmune, cardiovascular, and malignant disorders. Efficient in vivo delivery of small interfering RNA (siRNA) to immune cells could thus enable novel treatment strategies with broad applicability. In this report, we develop systemic delivery methods of siRNA encapsulated in lipid nanoparticles (LNP) for durable and potent in vivo RNA interference (RNAi)-mediated silencing in myeloid cells. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 41 publications
3
99
0
Order By: Relevance
“…4C). We also studied the silencing effects in four types of immune cells in spleen, peritoneal cavity, and bone marrow: macrophages (CD11b+), granulocytes (GR1+), B cells (CD19+), and T cells (TCRb) (29). cKK-E12 showed mild to medium silencing effects for all these immune cell lines in different organs at the dose of 1 mg/kg (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). We also studied the silencing effects in four types of immune cells in spleen, peritoneal cavity, and bone marrow: macrophages (CD11b+), granulocytes (GR1+), B cells (CD19+), and T cells (TCRb) (29). cKK-E12 showed mild to medium silencing effects for all these immune cell lines in different organs at the dose of 1 mg/kg (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, cKK-E12 was able to silence hepatocytes at low doses of administered FVII siRNA relative to endothelium (Tie2). Furthermore, in vivo comparison of cKK-E12 to the C12-200 formulation (ED 50 < 0.3 mg/kg for gene silencing of CD45) (29) shows that cKK-E12 was more selective toward liver parenchymal cell, with orders of magnitude lower doses needed to silence in hepatocytes compared with endothelial cells and immune cells in different organs (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…LNPs were used in this study because they have been shown to facilitate efficient delivery to hepatic and immune targets (23,(25)(26)(27). In the past few years, LNPs formulated with siRNAs against transthyretin (TTR) and proprotein convertase subtilisin/kexin type 9 (PCSK9) in rodents and nonhuman primates have produced promising preclinical results and several clinical trials involving LNPs are currently underway (28)(29)(30).…”
mentioning
confidence: 99%
“…This delivery system has an encouraging initial safety profile because repeated systemic administration did not affect body weight. In prior studies, performed in nonhuman primates and currently under phase III clinical trials, the LNP components that we used (except for the uninvestigated mAbs) showed satisfactory biocompatibility and little or no immune response (11,14,(16)(17)(18)24). However, more extensive toxicity studies are needed.…”
Section: Discussionmentioning
confidence: 99%